EDUKASI PASIEN DAN KELUARGA TERHADAP TINGKAT KEPATUHAN DIET HIPERTENSI DI PUSKESMAS TELUKNAGA KABUPATEN TANGERANG - Dea Mardiana; Shieva Nur Azizah Ahmad (Prosiding Simposium Nasional Multidisiplin (SinaMu), 2019)
Prevalation of hipertension suffers in indonesia always be increasing. In 2013 years for Riskesdas was 25,8% value for experienceing hipertension. Based on large data from outpatient illnes at kabupaten tangerang. For hipertension was second rank as many 53.708 peoples. Many factor was influece hipertension and inportant factor was food patient or food diet. Food diet such as salt diet, colestrol, hight fiber and low calorie. A significned increase in knowledge and attitute after the giving of health education about hipertension ( a hipertension diet education ). This research method used kuantitatif research with Quation Experiment methhod. And this plan used pre and post test without control (control in self). The location of the research at teluk naga public health center kabupaten Tangerang. for Hipertension suffers was 30-60 years old teluknaga public healthcenter kabupaten tangerang, with samples as many as 17 respondent. This research instrument used leaflet and pre and post questionnaires education. This result of this research was largely on education diet pretest 12 respondent or 70,6%. While education diet posttest was 15 respondent or 88,2%. The statistik is sig t (2-tailed) = 0,001 less than 0,005 that showing how significant influnce between education with hipertension diet at teluknaga public health center in kabupaten tangerang in 2018.Keywords : comfornity, education, diet, hipertension